The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1097/jcn.0000000000000423
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Rehospitalization and Delayed Decision Making

Abstract: We recommend a patient-centered approach to help HF patients identify and adequately self-manage symptoms. The strong association between high depressive symptoms and rehospitalization within 30 days as well as delayed decision making highlights the critical need for clinicians to carefully assess and address depression among HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
(40 reference statements)
4
39
0
1
Order By: Relevance
“…29 However, it was lower than that (50.7%) reported by Bhatt et al 30 The variation in prevalence may be attributed to the different screening tools and illness severity. Since depressive symptoms contribute to the increase in patients' hospitalizations, readmissions and mortality, and poor health-related quality of life, [7][8][9] it is essential to recognize and manage the depressive symptoms in patients with heart failure. This study showed that illness perceptions mediated the relationship between physical symptoms and depressive symptoms in heart failure patients, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, it was lower than that (50.7%) reported by Bhatt et al 30 The variation in prevalence may be attributed to the different screening tools and illness severity. Since depressive symptoms contribute to the increase in patients' hospitalizations, readmissions and mortality, and poor health-related quality of life, [7][8][9] it is essential to recognize and manage the depressive symptoms in patients with heart failure. This study showed that illness perceptions mediated the relationship between physical symptoms and depressive symptoms in heart failure patients, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Depressive symptoms have been found to contribute to increasing hospitalizations, readmissions and mortality and to a reduction in health-related quality of life in patients with heart failure. [7][8][9] To manage depressive and physical symptoms, it is essential to identify modifiable associated factors and the underlying mechanism between them in patients with heart failure.…”
mentioning
confidence: 99%
“…In addition to medical treatment, the implementation of standardized programs for the treatment of depression, such as the PROCEDE model, is shown to significantly improve symptoms of depression, quality of life, self-control and self-monitoring of patients [ 47 ]. Patients should be encouraged to take part in self-management and self-monitoring programs, in order to receie proper information on the HF symptoms and to be trained when to seek medical attention [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vignettes were embedded within the semi‐structured interview. Further details about the mixed methods study can be found in a previous publication (Xu, J. et al, ).…”
Section: Methodsmentioning
confidence: 99%